2008
DOI: 10.1002/bit.22041
|View full text |Cite
|
Sign up to set email alerts
|

Detailed understanding of enhanced specific antibody productivity in NS0 myeloma cells

Abstract: The understanding of how cellular productivity is modulated in cell lines is of significant importance in the biopharmaceutical industry. Often, single molecular mechanisms fail to fully explain how specific antibody productivity is enhanced during proliferation arrest. Previously, we reported that certain physiological changes occur when proliferation is arrested by p21(CIP1) over expression. In this work, we correlate physiological and molecular factors to enhance antibody productivity. Using biomass, cell v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
32
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 77 publications
4
32
0
Order By: Relevance
“…Excess LC mRNA is also a function of the greater stability of the LC transcript, as previously observed for an NS0 cell line producing cB72.3 Mab by Khoo and Al-Rubeai (2009). However, the reason for this differential transcript stability is currently unknown.…”
mentioning
confidence: 79%
See 1 more Smart Citation
“…Excess LC mRNA is also a function of the greater stability of the LC transcript, as previously observed for an NS0 cell line producing cB72.3 Mab by Khoo and Al-Rubeai (2009). However, the reason for this differential transcript stability is currently unknown.…”
mentioning
confidence: 79%
“…Excess LC mRNA and polypeptide production is a feature of many Mab production systems, both recombinant and natural Dorai et al, 2006;Khoo and Al-Rubeai, 2009;Lee et al, 2009;van Anken et al, 2003). Moreover, low LC:HC mRNA ratios, below 1.5, have also been associated with increased levels of Mab aggregation, a characteristic particularly undesirable in a production cell line (Lee et al, 2009).…”
mentioning
confidence: 97%
“…Besides soluble TNF-a, the transmembrane form of TNF-a demonstrates some unique biologic functions, such as cytotoxic activity and polyclonal B cell activation (Utsumi et al 1989). Antibodies (Abs) to soluble or membrane-associated forms of TNF-a have provided a new possibility to treat severe forms of rheumatoid and psoriatic arthritis, cutaneous Crohn's disease, psoriasis, and possibly other inflammatory skin diseases like Behcet's disease and pyoderma gangrenosum (Baldi et al 2005;Khoo and Rubeai 2008;Kohler 1980;Schlatter et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…This is in agreement with Lloyd et al 56 , who argued that the cell size is the major cellular determinant of productivity rather than the cell cycle phase. In addition to this, Edros et al 89 and Khoo and Al-Rubeai 90 showed that the increase in specific productivity is directly related to the increase in cell volume due to increase in transcription, translation, and secretion machinery. Kim et al 58 reported that the enhancement of the specific thrombopoietin productivity is linearly correlated with the increase in cell size for nine CHO cell clones generated using the same transfection process.…”
Section: Discussionmentioning
confidence: 95%
“…Furthermore, Kim et al 58 showed that the enhancement of the qp was linearly correlated with an increase in cell size for nine CHO cell clones generated using the same transfection process. Edros et al 89 and Khoo and Al-Rubeai 90 showed that the increase in qp was directly related to the increase in cell volume due to enhancement of the transcription, translation, and secretion machinery.…”
Section: Introductionmentioning
confidence: 99%